แนวทางการขยายความรับผิดของบริษัทภายใต้ศาลอาญาระหว่างประเทศ - วีระ ไกรกาบแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
There are cases of grave breaches under international criminal law causing severe damage to the international community in many aspects. A person who commits an international crime shall be individually responsible and liable for punishment within the jurisdiction of the International Criminal Court in accordance with Article 25 of The Rome Statute. Nonetheless, in the context of global economic interdependence, and related social, economic power and international political influencing Corporations and their business are major actors whom perpetrate international crimes for which the provisions of Article 25 are insufficient to prevent the offense. In particular, the current international atmosphere of thriving trade and investment increased relevant offense complexity .Corporate complicity in international criminal acts while there are many situation in which Corporations and their officials are direct and immediate perpetrators in international crime such as criminal responsibility in additional to "aiding and abetting" which includes deportation or forcible transfer after that Corporations takes advantage of the natural resources in order to return the maximum profit for its shareholders. The study has found that extending Corporations responsibility under the International Criminal Court is important for businesses in 21st century. As the field of international criminal law develops and as companies operate in new contexts. The international criminal law and its implementation in domestic and international jurisdiction will become ever more relevant to Corporations. Therefore, extending the provision of international criminal law (Rome status) provides a powerful and appropriate tool to deter and punish Corporations and their officials who participate crimes under international law.